Perempuan dan Kapitalisme - Amelia, Nur Indah; Ashmarita, Ashmarita (JURNAL KABANTI: Kerabat Antropologi, 2025)
This research is entitled "Women and Capitalism The purpose of this study was to determine and describe how the implications of the entry of peeled crab processing plan on people's lives especially in women lives who working at the plan. And this research uses the theory of the will to improve by Tania Murray Li, and The research method used in this research is descriptive qualitative with a feminist ethnographic approach. The results of this study indicate that the implications of the entry of peeled crab processing factories on people's lives are changes in livelihoods, lifestyles, environmental conditions, economic improvement, as well as the entry of the capitalist system which causes the exploitation of female labor. The wages received by workers are not proportional to the tight working hours charged, especially for overtime wages which are only paid with instant noodles. In addition, workers are also bound by debts to factory owners and unwritten rules made by factory owners. While working, the workers are not provided with facilities in the form of lunch, gloves that can protect their hands from sores and itching, and medicine if their hands are injured and itchy.